2006
DOI: 10.1099/vir.0.81583-0
|View full text |Cite
|
Sign up to set email alerts
|

Mixed infection with multiple strains of murine cytomegalovirus occurs following simultaneous or sequential infection of immunocompetent mice

Abstract: As with human cytomegalovirus (HCMV) infection of humans, murine CMV (MCMV) infection is widespread in its natural host, the house mouse Mus domesticus, and may consist of mixed infection with different CMV isolates. The incidence and mechanisms by which mixed infection occurs in free-living mice are unknown. This study used two approaches to determine whether mixed infection with MCMV could be established in laboratory mice. The first utilized two naturally occurring MCMV strains, N1 and G4, into which the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 54 publications
1
53
0
Order By: Relevance
“…However, superinfection has been observed in mice, rhesus macaques, and humans (23)(24)(25). Widespread use of CMV vectors as tumor vaccines would largely depend on the ability to induce a superinfection in already infected individuals.…”
Section: Construction and Characterization Of Recombinant Mcmv-gp100 mentioning
confidence: 99%
See 1 more Smart Citation
“…However, superinfection has been observed in mice, rhesus macaques, and humans (23)(24)(25). Widespread use of CMV vectors as tumor vaccines would largely depend on the ability to induce a superinfection in already infected individuals.…”
Section: Construction and Characterization Of Recombinant Mcmv-gp100 mentioning
confidence: 99%
“…CMV belongs to the Herpesviridae family, and the following unique characteristics make CMV a promising cancer vaccine vector: (i) CMV establishes a lifelong, asymptomatic infection in immunocompetent hosts; (ii) a remarkable characteristic of CMV infections is that a robust superinfection is observed despite the presence of preexisting CMV-specific immunity, and thus individuals who may already harbor latent CMV can be reimmunized with CMV-based vaccines (23)(24)(25); (iii) cloning of the CMV genome as a bacterial artificial chromosome makes it possible to introduce multiple tumor antigens into the CMV vector; (iv) CMV infection induces a strong inflammatory innate immune response followed by a robust polyfunctional CD8 T-cell expansion, which makes CMV a potentially ideal T-cell-based cancer vaccine vector; (v) in mice and in humans, a process called memory inflation continues long after the establishment of latency, in which CMV-specific CD8 T-cell populations proliferate for the life of the host (26)(27)(28)(29), and a large percentage of these "inflationary" CD8 T cells are functional as exhibited by their ability to secrete multiple cytokines; and (vi) the CMV-specific CD8 þ T cells are distributed widely in lymphoid and nonlymphoid organs, such as the lung, liver, and brain; therefore, CMV vaccines could be used to target metastases in different organs.…”
Section: Introductionmentioning
confidence: 99%
“…MCMV infection in wild M. m. domesticus mice is dependent on mouse population density (9,10) and is positively correlated with the age of the individuals, suggesting cumulative exposure over time (11). Multistrain MCMV infections are common in free-living mice (5,12). The strains are acquired by immunocompetent mice through simultaneous or successive infections (12).…”
mentioning
confidence: 99%
“…Multistrain MCMV infections are common in free-living mice (5,12). The strains are acquired by immunocompetent mice through simultaneous or successive infections (12). A study on enclosure populations of M. m. domesticus has shown that MCMV had minimal or no impact on mouse survival or breeding when individuals were infected with a single strain but that young males infected with two viral strains had a 20% reduction in survival (13).…”
mentioning
confidence: 99%
“…Indeed, a onetime exposure to various viruses besides HIV-1 seem to confer no or only partial protection, allowing a secondary infection to occur in the presence of another viral strain against which an adaptive immune response has been mounted. Members of the herpes virus family, such as herpes simplex virus 1 [78] or 2 [79], Epstein-Barr virus [80], varicella zoster virus (reviewed in [81]), human herpes virus 8 [82], and notably cytomegalovirus (CMV) [83][84][85][86][87][88], provide remarkable examples of secondary infections in previously chronically infected hosts. For the scope of this review, we will limit the discussion to a few viruses that have a major impact on global health.…”
Section: Implications For Hiv-1 Vaccine Design: Lessons From Other VImentioning
confidence: 99%